WILSON PLOT METHOD TO OBTAIN NUSSELT NUMBER FOR A PLATE HEAT EXCHANGER - Ferreira, D. dos S.; Mantelli, M.; Milanese, F. (Revista de Engenharia Térmica, 2020)
Plate heat exchangers are devices commonly used in industry due to their high efficiency and ease cleaning. Although its first use was in food sector, nowadays this equipment can be found in most industrial segments, like chemistry and oil industry. Due the facility of fabrication, the corrugated gasket plate heat exchanger is amply utilized in those segments, however, its mathematical analysis present non-agreement between the authors, because of the different plate models and operation settings. Thus, the main objective of this work is to study the application of the Wilson-Plot method to analyze the thermal behavior of an elemental plate heat exchanger, and verify if the operation temperature has significant influence in the thermal behavior of the plate heat exchanger.